Determinan Kinerja Keuangan Pra–Pasca Merger Perusahaan Telekomunikasi Indonesia: Analisis CR, ROA, dan DER - Niken Ayu Lestari; Eko Hariyanto; Iwan Fakhruddin; Nur Isna Inayati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the factors that influence financial performance by comparing financial performance (ROE) and the impact of liquidity (current ratio/CR), profitability (ROA), and solvency (DER) in telecommunications companies in Indonesia before and after mergers. The research population includes all telecommunications companies listed on the Indonesia Stock Exchange (IDX) that underwent mergers or business integrations during the period 2006-2025, with a total of 56 pre-merger observations and 55 post-merger observations. The data analysis techniques used include descriptive statistics, Paired Sample T-test, and multiple linear regression analysis. The results of the difference test show a significant difference in financial performance between the pre- and post-merger periods (Sig. = 0.003), where the average ROE decreased from 0.09728 to 0.05510. The regression results prove that in the pre-merger period, only ROA and DER had a significant positive effect on ROE. However, in the post-merger period, liquidity (CR) showed a significant negative effect on ROE (Sig. = 0.006), while ROA and DER continued to have a significant positive effect. These results indicate that after the merger, unproductive current assets can reduce ROE, reflecting integration challenges and agency costs in the short term. Practically, these findings indicate that a merger does not automatically translate into higher shareholder returns in the short run; firms should optimize the use of current assets and accelerate operational synergy realization to avoid idle liquidity and reduce integration costs.